(untitled) (Global Journal of Human-Social Science, 2017)
Throughout the world today, depletion of natural resources is among the major problems facing human beings. Land degradation, especially in the highlands, has been identified as the most serious environmental problem in Ethiopia. The Hararghae highlands in Eastern Ethiopia, Tigrai, Wollo, and Semen Shoa highlands in the north and the Gamo-Gofa highlands and the Bilate River basin, which starts in eastern slopes of Gurage highlands and stretches through eastern Hadiya and Kembatta highlands are some of the seriously eroded/degraded land surfaces in Ethiopia. The dominant man induced causes of land degradation in Ethiopia are poor farming practices, population pressure, overgrazing, over cultivation, soil erosion, deforestation, salinity and alkalinity problems, and the use of livestock manure and crop residue for fuel as energy resource of the rural households. The recorded annual soil erosion (surface soil movement) in Ethiopia ranges from low of 16 tons/ha/yr to high of 300 tons/ha/yr depending mainly on the slope, land cover, and rainfall intensities. The total estimated annual soil loss (surface soil movement) from the cultivated, range and pasture lands (780,000 km 2 ) in Ethiopia is estimated to range from low of 1.3 to an average of 7.8 billion metric tons per year. Study put the degraded area on the highlands at 27 million ha of which, 14 million hectares is very seriously eroded with 2 million ha of this having reached a point of no return, and the soil depth is so reduced that the land is no longer able to support any vegetative cover.